MiR-200b regulates cellular senescence and inflammatory responses by targeting ZEB2 in pulmonary emphysema. Issue 1 (1st January 2020) - Shen, Zhiming; Xuan, Wenting; Wang, Huanhuan; Sun, Fei; Zhang, Chengxin; Gong, Qian; Ge, Shenglin
Abstract: Smoking is an important factor in the pathogenesis of chronic obstructive pulmonary disease (COPD), which is commonly characterised by cellular senescence and inflammation. Recently, miR-200b has emerged as an important target to cure lung disease; however, the function of miR-200b in reducing cellular senescence and inflammatory responses has not been reported. In this study, we found that miR-200b was downregulated in the lungs of COPD model mice, and its expression is correlated with cellular senescence and inflammatory responses. We hypothesised that miR-200b may be a potential novel therapy for treating COPD. We performed senescence-Associated-β-galactosidase (SA-β-GAL) staining, western blot, qRT-PCR and ELISA; our data suggested that miR-200b is an anti-aging factor in the lungs that is involved in inflammatory responses. We also confirmed that ZEB2 (Zinc finger E-box binding homeobox 2) is a target gene of miR-200b using luciferase reporter assay. In addition, we verified the function of ZEB2 in cellular senescence and inflammatory responses through transfection experiments. Moreover, we found that the protective effects of miR-200b are inhibited when cells overexpress the ZEB2 protein. In conclusion, our results suggest that miR-200b may attenuate cellular senescence and inflammatory responses by targeting ZEB2 in pulmonary emphysema.